Enhanced Photocatalytic Hydrogen Production by Adsorption of an [FeFe]‐Hydrogenase Subunit Mimic on Self‐Assembled Membranes. Issue 4 (12th January 2016) - Troppmann, Stefan; Brandes, Eva; Motschmann, Hubert; Li, Fei; Wang, Mei; Sun, Licheng; König, Burkhard
Abstract: Self‐assembled vesicles with membrane‐embedded or adsorbed ruthenium polypyridine complexes were further functionalized by the adsorption of an [FeFe]‐hydrogenase subunit mimic to the membrane interface enhancing the photocatalytic hydrogen production in water under acidic conditions. The resulting two‐dimensional membrane assembly places the photosensitizer and hydrogen‐evolving diiron complex in close proximity resulting in a six‐ to twelvefold increase in the turnover number as compared to the same system in the absence of lipid membranes. The interface assembly then enables the combining of hydrophilic and hydrophobic catalytic entities for light‐driven proton reduction in acidic water and provides a flexible method for membrane functionalization. Abstract : A flexible method for the functionalization of vesicles for visible‐light‐driven H2 generation by adsorption of catalytically active complexes to the membrane interface is described (see the figure). The interface self‐assembly provides close proximity of the catalytic subunits and significantly increases the photocatalytic hydrogen production in comparison to non‐vesicular systems.